Formation of Identity in Sport: A Systematic Review (Research, Society and Development, 2020)
This study aimed to conduct a systematic review of the literature on athletes’ identity formation, including researches from 1978 to 2014. A total of 121 studies were evaluated and reported in three sections: the methodological characteristics of the studies, variables associated with identity and main theoretical supports. Study samples ranged from 1 to 2.000 participants. These studies comprised a range of several competitive levels and modalities, in different genders and research methods. Variables associated with identity were categorized as follows: demographic questions, moral atmosphere, psychosocial support, health/injury problems, life control, educational status, self-perception, motivation, personal/career development, sport commitment, eating attitudes, coping, retirement and burnout. The current status of this area, limitations, suggestions for practice and future research are discussed.